Displaying morally responsible motherhood: lone mothers accounting for work during non-standard hours. (1st November 2020) - Moilanen, Sanna; May, Vanessa; Sevón, Eija; Murtorinne-Lahtinen, Minna; Laakso, Marja-Leena
Abstract : This study examined how lone mothers rationalise their work during non-standard hours (e.g., evenings and weekends), which they perceive as problematic in terms of child wellbeing, and thereby as violating the culturally shared moral order of 'good' motherhood. The data comprise interviews with 16 Finnish lone mothers, analysed as accounts, with a special focus on their linguistic features. The mothers displayed morally responsible motherhood through: (1) excusing work during non-standard hours as an external demand; (2) appealing to an inability to act according to good mothering ideals; (3) using adaptive strategies to protect child wellbeing; and (4) challenging the idea of risk. Our findings indicate that the moral terrain lone mothers must navigate is shaped by the ways in which their family situation contravenes powerful ideologies around good mothering, while their efforts to resist the ensuing stigma are constrained by the need to engage in work during non-standard hours.